Tuberculosis vaccines — perspectives from the NIH/NIAID Mycobacteria vaccine testing program. (August 2017) - Izzo, Angelo A
Highlights: Expanding knowledge of the immune response to M. tuberculosis infection is improving the design of vaccine candidates. The identification of novel pathways that may be involved in killing M. tuberculosis is critical for vaccine development. Understanding the network of interactions between immune cells and signals will provide a significant breakthrough in developing an effective vaccine. Abstract : The development of novel vaccine candidates against infections with Mycobacterium tuberculosis has highlighted our limited understanding of immune mechanisms required to kill M. tuberculosis . The induction of a Th1 immunity is vital, but new studies are required to identify other mechanisms that may be necessary. Novel vaccines formulations that invoke effector cells such as innate lymphoid cells may provide an environment that promote effector mechanisms including T cell and B cell mediated immunity. Identifying pathways associated with killing this highly successful infectious agent has become critical to achieving the goal of reducing the global tuberculosis burden.